Molecular differentiation and phylogenetic relationships of three Angiostrongylus species and Angiostrongylus cantonensis geographical isolates based on a 66-kDa protein gene of A. cantonensis (Nematoda: Angiostrongylidae) - Eamsobhana, Praphathip; Lim, Phaik Eem; Zhang, Hongman; Gan, Xiao Xian; Yong, Hoi Sen (Elsevier, 2010)
The phylogenetic relationships and molecular differentiation of three species of angiostrongylid nematodes (Angiostrongylus cantonensis, Angiostrongylus costaricensis and Angiostrongylus malaysiensis) were studied using the AC primers for a 66-kDa protein gene of A. cantonensis. The AC primers successfully amplified the genomic DNA of these angiostrongylid nematodes. No amplification was detected for the DNA of Ascaris lumbricoides, Ascaris suum, Anisakis simplex, Gnathostoma spinigerum, Toxocara canis, and Trichinella spiralis. The maximum-parsimony (MP) consensus tree and the maximum-likelihood (ML) tree both showed that the Angiostrongylus taxa could be divided into two major clades - Clade 1 (A. costaricensis) and Cade 2 (A. cantonensis and A. malaysiensis) with a full support bootstrap value. A. costaricensis is the most distant taxon. A. cantonensis is a sister group to A. malaysiensis; these two taxa (species) are clearly separated. There is no clear distinction between the A. cantonensis samples from four different geographical localities (Thailand, China, Japan and Hawaii); only some of the samples are grouped ranging from no support or low support to moderate support of bootstrap values. The published nucleotide sequences of A. cantonensis adult-specific native 66 kDa protein mRNA, clone L5-400 from Taiwan (U17585) appear to be very distant from the A. cantonensis samples from Thailand, China, Japan and Hawaii, with the uncorrected p-distance values ranging from 26.87% to 29.92%.